2022
DOI: 10.1021/acsomega.2c03401
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Nylon 6 Fabric as an Efficient and Recyclable Catalyst for Knoevenagel Condensation

Abstract: Nylon 6 fabrics were chemically modified via reduction with BH 3 for being functionalized as heterogeneous base organocatalysts for Knoevenagel condensation. The results of FTIR, XPS, and SEM indicated the successful modification of nylon 6 fabrics. With a low catalytic dosage of 6.6 mol % and a short reaction time (2 h), the fabric catalysts were well applicable to Knoevenagel condensation of a wide range of substrates and up to 98% yield could be obtained. In addition, the fabric catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Mechanical testing revealed that the bending modulus of PA10T‐F 2 M 8 increased to 1553.66 MPa, representing an approximately 50.47% increase compared to PA10T. These findings highlight the notable improvements in the overall mechanical properties of the composites with the incorporation of fillers 51 . In conclusion, the wear‐resistant PA10T‐FM composites are innovative heat‐resistant engineering plastics exhibiting outstanding wear resistance.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Mechanical testing revealed that the bending modulus of PA10T‐F 2 M 8 increased to 1553.66 MPa, representing an approximately 50.47% increase compared to PA10T. These findings highlight the notable improvements in the overall mechanical properties of the composites with the incorporation of fillers 51 . In conclusion, the wear‐resistant PA10T‐FM composites are innovative heat‐resistant engineering plastics exhibiting outstanding wear resistance.…”
Section: Discussionmentioning
confidence: 71%
“…These findings highlight the notable improvements in the overall mechanical properties of the composites with the incorporation of fillers. 51 In conclusion, the wearresistant PA10T-FM composites are innovative heatresistant engineering plastics exhibiting outstanding wear resistance. Furthermore, they hold promising prospects for a wide range of applications in various fields.…”
Section: Discussionmentioning
confidence: 95%
“…This is due to the long strands and orderly hydrogen bonds in nylon. Additionally, these membranes are re-usable as their pores remain intact after washing [ 48 , 49 ]. In the present work, capillary action is used for the primary transfer technique, taking advantage of this property.…”
Section: Resultsmentioning
confidence: 99%
“…7a depicts the proposed reaction mechanism for access to α,β-unsaturated nitrile derivatives based on the literature. 6,79 The key factor for the proposed mechanism is that acidic sulfonic sites enable the Knoevenagel coupling by polarizing the carbonyl group of benzaldehyde, where it can coordinate with oxygen and further be attacked by the pronucleophile-like malononitrile or ethyl cyanoacetate. Afterward, a water molecule was eliminated to yield the α,β-unsaturated product.…”
Section: Resultsmentioning
confidence: 99%